Moves - Spaces - Places The Life Worlds of Jamaican Women in Montreal. An Ethnography - Johnson, Lisa (Kultur und soziale Praxis, 2021)
In the complex and multi-layered process of migration and identity-building, classical migration theories and approaches of transnationalism seem no longer able to grasp how belonging and home are to be found in movement. This ethnography leads the reader into the lives of five Jamaican women in Montreal; their daily practices and experiences, their spaces of communion, their memories and projections for the future. Lisa Johnson sheds light on the mobile biographies and migratory agency of her interlocutors by following the intricate mental and physical trajectories of their deep-rooted yearning to return home.